My Personal Meetings and Business Contacts in Absentia with V.V. Davidov - Vasilev V.K (Moscow State University of Psychology and Education, 2020)
The article shares opinions and assessments about the personality and creative and scientific work of V.V. Davydov, as the author - a Bulgarian psychologist - is based on his personal meetings with V.V. Davydov, their common endeavors, as well as the experienced influence of their contacts - direct and extramural - with an outstanding Russian psychologist and his students and followers.